2022
DOI: 10.3748/wjg.v28.i38.5602
|View full text |Cite
|
Sign up to set email alerts
|

Timing of endoscopic retrograde cholangiopancreatography in the treatment of acute cholangitis of different severity

Abstract: BACKGROUND The optimal timing of endoscopic retrograde cholangiopancreatography (ERCP) in acute cholangitis (AC) is uncertain, especially in patients with AC of varying severity. AIM To report whether the timing of ERCP is associated with outcomes in AC patients with different severities. METHODS According to the 2018 Tokyo guidelines, 683 patients who met the definite diagnostic criteria for AC were retrospectively identified. The results we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…However, this study included all grades of acute cholangitis together. 5 The findings and hypotheses of a recent retrospective study by Huang et al 14 are interesting. In this study, subgroup analyses were performed in all patients with severe, moderate and mild cholangitis.…”
Section: Discussionmentioning
confidence: 94%
“…However, this study included all grades of acute cholangitis together. 5 The findings and hypotheses of a recent retrospective study by Huang et al 14 are interesting. In this study, subgroup analyses were performed in all patients with severe, moderate and mild cholangitis.…”
Section: Discussionmentioning
confidence: 94%
“…Second, recent clinical studies have produced controversial results in terms of early implementation of BD for patients with grade III AC. In addition to the study by Huang et al [ 3 ] discussed herein (BD at ≤ 48 but not ≤ 24 h), another retrospective study by Lu et al [ 7 ] showed that BD is recommended at 24 h of admission for patients with grade III AC and within 12 h for those with AC accompanied by neurological or cardiovascular dysfunction. However, a study by Becq et al [ 8 ] using a propensity score matching approach indicated that the use of BD within 6h or 12 h of AC onset was not associated with better clinical outcomes, but possibly reduced readmission rates.…”
Section: To the Editormentioning
confidence: 89%
“…We recently became extremely interested in a retrospective study by Huang et al [ 3 ] published in the October 2022 issue of the World Journal of Gastroenterology . This was a high-quality observational study with a Newcastle-Ottawa Quality Assessment Scale score of 7 (3, 2, 2)[ 4 ].…”
Section: To the Editormentioning
confidence: 99%
See 2 more Smart Citations